Between Shari’ah and Secularism: Tunisia’s Code of Personal Status as Contextualized Ijtihad in Islamic Family Law - Maghfiroh, Kholifatul; Ali; Dyah Syifa Herawati; Septi Apriliyani P; Naila Umdah Zuhaidah (Universitas Islam Negeri (UIN) Mataram, 2025)
This study examines the controversies surrounding Islamic family law in Tunisia, situated at the intersection of Shari'ah tradition and state-led modernization. Tunisia is widely recognised as a pioneer among Muslim-majority countries for its progressive reform of family law through the enactment of the Majallah al-A?wal al-Shakh?iyyah (Code of Personal Status, CPS) in 1956. This codification outlawed polygyny, granted women the right to petition for divorce, and enshrined principles of gender equality - measures that have provoked sustained debate among jurists, Islamic activists, and the broader public. This study draws library research. The research reveals that Tunisian family-law reform represents a contextualised exercise of ijtihad, aimed at reconciling Islamic objectives with contemporary social imperatives. By illuminating the conflict between tradition and modernity in Tunisian jurisprudence, this article contributes to global scholarship on the relationship among religion, state, and law in contemporary Muslim societies